â€œTHE BOARD GAME TO DEVELOP STUENTSâ€™ SPEAKING SKILL FOR HIGH AND LOW ACHIEVERSâ€ The Case at The Eleventh Graders of Ihsaniyah Senior High School of Tegal In The Academic Year of 2013-2014 (Universitas Negeri Semarang, 2014)
This study was investigated the effectiveness of the board game for High and Low Studentsâ€™ achievement in speaking. The objects of this study were conducted at the eleventh graders; the samples of the research were from two classes, each class consisting of 26 students for experimental group and 26 students for control group. Each class was divided into two groups based on their level of achievement (high and low). This research applied a quantitative method with a factorial design. The data were analyzed by using ANOVA and Tuckey test. The result of the study showed that: (1) there is no significant difference between using board game and drilling to the high achievers ;(2) There is a significant difference between using board game and drilling to the low achievers;(3) There is a significant difference of using board game to the high and low achievers; (4) There is a significant difference of using drilling to the high and low achievers; (5) There is a significant interaction of teaching technique (board game and drilling) and types of students of achievement (high and low).